Liver Regenerative and Hepatoprotective Effects OF Moringa Oleifera Extract in the Liver Fibrosis Animal Model - Supriono Supriono (Journal of Global Pharma Technology, 2020)
Objective: This study was conducted to know the liver regenerative and hepatoprotective effects of Moringa oleifera (MO) in the animal models of liver fibrosis. Methods: The study was a randomized post-test only controlled group design. Male Rattus novergicus of liver fibrosis caused by induction of CCl4 was treated with extract of (MO). Histological of the liver tissue with hematoxylin and eosin (H&E) staining were investigated by a light microscope. We calculate the number of hepatocytes expressing MDA and cytokeratin-7 (CK-7) in liver tissue using the immunohistochemical analysis. Results: Induction of CCL4 for 14 weeks results in liver fibrosis (METAVIR score F-3) and improves by the administration of MO. The number of hepatocytes expressing MDA in liver fibrosis models sevenfold higher than normal models and significantly lower after treated with MO. ALT and AST in the treated models significantly lower than in the liver fibrosis models. On the other hand, the number of hepatocytes expressing CK-7 in both normal and liver fibrosis models was lower. The CK-7 significantly higher after the administration of MO. Many ductular reactions develop in the treated animal models. Conclusions: in our knowledge, this is the first study reported a liver regenerative effect of MO in the liver fibrosis, beyond its hepatoprotective effect. The mechanism of liver regenerative probably through a hepatic progenitor cell proliferation. Keywords: Moringa oleifera, liver fibrosis, liver regenerative, CK7, MDA.